The study of parent-regeneration relationships for wild cherry (Prunus avium L.) in Hyrcanian forests - Bahman Kiani; Kiyan Yegandoost (Journal of Forest Science, 2021)
The regeneration of forest trees is affected by the presence, dispersion pattern and specifications of parent trees. These effects were investigated and modelled in hardwood forests in the north of Iran. To do so, at first, fifty plots, each with a total area of 0.1 ha, were identified. Four subplots with a radius of two meters were then stabilized in each plot. The height and the root collar diameter of all the cherry seedlings were measured. Likewise, the diameter, basal area, and distance from the plot centre were appraised in the parent trees. The correlation and regression analyses were performed to evaluate the effects and to construct the models, respectively. The results showed that there was a positive and significant relationship between the presence, abundance, mean diameter, and total basal area of parent trees and the presence and abundance of seedlings. The logistic regression showed that the models based on the mean diameter of parent trees and abundance of parent trees could significantly predict the presence of regeneration. Only in 10% of the sample plots was the regeneration recorded without the presence of a parent tree. Due to the small number of established seedlings, while maintaining the existing parent trees, especially large trees, it is necessary to consider the proper management methods to promote and protect their regeneration. We recommend completing the natural regeneration of wild cherry by artificial regeneration and creating well-dimensioned canopy gaps.